Effects of Zinc and Aluminum on the CuO Crystalline Size for Direct Dimethyl Ether Synthesis from Syngas - Thongkam, Montree; Piyabunditgul, Nanchapak; Trisupakitti, Somsuk; Rungrojchaipon, Pesak (My University, 2021)
The effects of zinc and aluminum on the CuO crystalline size for direct dimethyl ether (DME) synthesis from syngas were investigated. Metal oxide catalysts were synthesized with various molar ratios of CuO by the precipitation method, and by the co-precipitation method with CuO/ZnO (CZ), CuO/ZnO/Al2O3 (CZA), and CZA at ratios of 1:1, 2:2:1, and 6:3:1, respectively. The acid catalysts (γ-Al2O3, HZSM-5) were added to the metal oxide catalysts by physical mixing. The catalysts were characterized morphologically and their acidities were determined. Loading of zinc and aluminum at different ratios showed that CZA (2:2:1) gave the smallest CuO crystalline size, appropriate for the methanol synthesis reaction. γ-Al2O3 has a weak to moderate acidity range, suitable for DME synthesis. Moreover, the bifunctional catalyst, CZA (2:2:1)/γ-Al2O3, had the highest surface area as well as the highest %CO conversion and %DME selectivity.
Keywords: Aluminum; Bifunctional catalyst; Copper oxide; CuO/ZnO/Al2O3; Dimethyl ether; Zinc